PENYULUHAN PENTINGNYA MELAKUKAN PEMERIKSAAN TUMBUH KEMBANG BALITA - Aditia, Dita Selvia; Destri, Yuhelva; Ristiyana, Septi; Wahyuni, Iin; Xanda, Adhesty Novita (Universitas Aufa Royhan Di Kota Padangsidipuan, 2023)
According to WHO (2012), the number of people suffering from malnutrition in the world has reached 104 million children and malnutrition is still the cause of all child deaths throughout the world. South Asia is the region with the largest prevalence of malnutrition in the world, namely 46%. Nutrition in toddlers is influenced by socioeconomic factors and socio-cultural background related to diet and nutrition. Insufficient nutrition in the first five years of life has an irreversible impact on physical, mental and brain growth and development. The causes of malnutrition in children are influenced by many factors and are multidimensional, such as socio-economic factors and socio-cultural background as external factors and the health status of toddlers as internal factors. Kabeta, et al. (2017). As is known, increasing socio-economic status and exclusive breastfeeding for 6 months is associated with a decrease in the prevalence of malnourished children under five. Anuradha, et al. (2014). This activity will be held on May 23 2023 in Bayas Jaya Pesawaran Village. Based on the results, the number of mothers who took part in this activity was 26 mothers who had babies and toddlers. The tools and materials used in this activity are leaflets and media for conducting outreach. Based on observations made, there is increased knowledge and understanding of mothers about the benefits of counseling on the importance of carrying out growth and development checks on toddlers through leaflet media and lecture methods so that mothers are educated on the importance of carrying out growth and development checks on toddlers by continuing to monitor the health of their babies and toddlers at posyandu or at health service locations.